Christopher Dawson : a cultural mind in the age of the Great War - Stuart, Joseph T. (The Catholic University of America Press, 2022)
"The English historian Christopher Dawson (1889-1970) was the first Catholic Studies professor at Harvard University and has been described as one of the foremost Catholic thinkers of modern times. Joseph T. Stuart argues that through Dawson's study of world cultures, he acquired a "cultural mind" by which he attempted to integrate knowledge according to four implicit rules: intellectual architecture, boundary thinking, intellectual asceticism, and intellectual bridges. Dawson responded to the cultural fragmentation after the Great War (1914-1918) through this multilayered approach to culture, which was an instantiation of John Henry Newman's philosophical habit of mind. Stuart demonstrates how Dawson formed his cultural mind practicing an interdisciplinary science of culture involving anthropology, sociology, history, and comparative religion, and applied his cultural thinking to problems in politics and education"--